2020
DOI: 10.1007/s11121-020-01116-4
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Replication of the Effectiveness of the KiVa Antibullying Program: a Randomized Controlled Trial in the Netherlands

Abstract: This study evaluates the effectiveness of the KiVa antibullying program in the Netherlands through a randomized controlled trial of students in grades 3-4 (Dutch grades 5-6). The sample involved 98 schools who volunteered to participate in the research, with 245 classes and 4383 students at the baseline (49% girls; M age = 8.7 years), who participated in five measurement waves, collected in three consecutive school years. After the baseline, two-thirds of the schools were assigned to the intervention condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
0
33
0
1
Order By: Relevance
“…Second, we obtained IRB approval by the Ethics Committee from the Department of Sociology for a pilot study in four schools on the practical use and formulation of the questions, and the duration of filling in the questionnaire. After the pilot, we adjusted the questions and administered them together with measures of adjustment correlates to students in a larger sample of schools that took part in the eleventh wave of the ongoing study on the KiVa anti‐bullying program (Kärnä et al, ) in the Netherlands (Huitsing et al, under review). Schools were selected based on the criteria that they had distributed informed consent forms to parents and that they administered the bi‐annual questionnaire at about the same time.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we obtained IRB approval by the Ethics Committee from the Department of Sociology for a pilot study in four schools on the practical use and formulation of the questions, and the duration of filling in the questionnaire. After the pilot, we adjusted the questions and administered them together with measures of adjustment correlates to students in a larger sample of schools that took part in the eleventh wave of the ongoing study on the KiVa anti‐bullying program (Kärnä et al, ) in the Netherlands (Huitsing et al, under review). Schools were selected based on the criteria that they had distributed informed consent forms to parents and that they administered the bi‐annual questionnaire at about the same time.…”
Section: Methodsmentioning
confidence: 99%
“…The prevention involves universal actions targeted at all students, with teacher training, theme lessons, virtual learning environment for students, KiVasymbols such as recess vests and posters, and information for parents (through flyers, an online booklet, and newsletters). Intervening by means of indicated actions is aimed at ongoing bullying and targeted at students who have been identified as targets or perpetrators of bullying (see for more information: Huitsing et al 2019).…”
Section: Kiva Anti-bullying Programmentioning
confidence: 99%
“…The effectiveness of KiVa was studied in a randomized controlled trial in 2012-2014 in target grades 3-4 of Dutch primary schools (Dutch grades 5-6). The research into the effectiveness of KiVa in the Netherlands showed that victimization of bullying had declined significantly more at KiVa schools than at control schools, both after 1 and 2 years of implementation (Huitsing et al 2019; see also: Kaufman et al 2018). More specifically, the number of children who were bullied monthly, weekly, or daily at KiVa schools decreased with 64% after 2 years of implementing the intervention (compared with a 53% decrease in control schools).…”
Section: Kiva Anti-bullying Programmentioning
confidence: 99%
See 2 more Smart Citations